The Effect of Adding Iodine to the Feed to Increase Growth and Survival Rate of Carp Seeds (Cyprinus carpio) - Ayu Nirmaniar Fadliani; Ayu Adhita Damayanti; Ibadur Rahman (Universitas Mataram, 2020)
One of the factors that greatly influence the successful growth of cultivated fish is feed. The aim of this study was to examine the effect of iodine addition on the growth and survival rate of carp (Cyprinus carpio) seeds. This study used a completely randomized design (CRD) method with 4 treatments and 3 replications. 10 fish per unit each, with treatment P0 (feed without adding iodine), P1 (feed + iodine at a dose of 10 mg / kg), P2 (feed + iodine at a dose of 20 mg / kg), P3 (feed + iodine at a dose of 30 mg / kg). The results showed that there was no significant effect (p> 0.05) on the growth rate, feed conversion and survival rate of goldfish. So it can be concluded that the addition of iodine in feed supplementation up to a dose of 30 mg / kg does not have a significant effect on the growth rate of length and absolute weight, feed conversion, survival rate and iodine content in the body of goldfish (Cyprinus carpio). The best recommended dose of iodine for growth is 20 mg / kg of feed, although the results were not significantly different for growth. However, it can have an effect on the iodine content in the body of goldfish.